Menjaga Kesehatan Masyarakat melalui Perbaikan Lingkungan Kampung di Kota Surabaya Tahun 1910-1940 - Samidi M. Baskoro; Noviani Mariyatul Hakim (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2021)
The colonial government began to pay attention to the kampongs in the city of Surabaya at the beginning of the 20th century. At that time, the bad condition of the kampung environment was caused by the settlements developing naturally without water channels. Poor environmental conditions can also have an impact on public health. This is evident from the bubonic plague that began in 1910. The article discusses how the city government maintained the public health in that time. Historical data to explain this problem were collected through historical research procedures, such as heuristics, verification, interpretation. The historical data were on waste management, drainage improvement, and kampongs improvement as evidence that the government is trying to maintain public health. The long-term impact of environmental improvement was the stability of a healthy environment. Public health problems gave rise to joint action between the government and the society. The important action taken was the management of the settlement environment for the realization of normal public health.